The business of plastic surgery - Korman, Joshua M. (2019)
Cut through the fog and set your compass for success! The Business of Plastic Surgery: Navigating a Successful Career. 2nd Edition is essential reading for every plastic surgeon. Chart your own course through the arc of a rewarding career. In this comprehensive guide. learn practical strategies to excel in private. group. and academic practice. Master business skills from digital marketing to evaluating new technologies. Discover how to fight physician burnout and strike a work–life balance for a truly satisfying future. Topics rarely covered include thoughtful perspectives on underrepresentation by race. ethnicity. sexual orientation. and gender. An all-star list of contributors offers secrets in navigating stormy seas